Kritisches Denken im islamischen Religionsunterricht: Eine theologische und religionspädagogische Herausforderung jenseits des Haram-halal-Konzepts - Yagdi, Senol (Österreichisches Religionspädagogisches Forum, 2024)
The promotion of critical thinking in children and adolescents is a crucial factor in the curricula of the Austrian education system, not least in religious education. The empirical study presented here collects and analyses the goals, attitudes, and approaches to this aspect voiced by Islamic religious education teachers in group discussions. Their experiences and orientations regarding the promotion of students’ reflectivity and power of judgement are evaluated with a view to religious education impulses.